Undergraduate Students’ Perceptions of Tourism and Hospitality Career Education in Ghana - Yirbekyaa, Evelyn K.; Kuuder, Conrad-J. Wuleka; Mohammed, Issah (Advances in Social Sciences Research Journal, 2021)
The purpose of this study was to explore students’ perceptions of tourism and hospitality career education in three universities that run undergraduate programmes in Ghana, namely: the University of Cape Coast (UCC), University of Energy and Natural Resources (UENR) and the University for Development Studies (UDS). Final year students totaling 128 students were contacted through questionnaire and results analyzed employing SPSS. The study revealed that 45% respondents from the UCC did not want to work in the industry after graduation. A greater number of respondents, 85% in UCC, 90% in UENR and 92% in UDS believed a decision to invest in tourism and hospitality education career was worthwhile. Contrary to the above 50% of all respondents surveyed in the three institutions did not believe one could make good income whilst working in the industry. It is suggested that career counselling sessions be organized by tourism and hospitality industry players in the universities to woo students’ interest in the sector.